Determining the suitable CO2 laser based technique for microchannel fabrication on PMMA. (July 2021) - Prakash, Shashi; Kumar, Subrata
Highlights: Five different CO2 laser microchanneling processes have been compared. Single-pass processing results in highest surface roughness. Multi-pass and defocused processing produce clean and smooth microchannels. Raster scanning with mask can produce rectangular microchannels. Abstract: CO2 lasers are commonly used in fabricating microchannels on Polymethyl methacrylate (PMMA) substrate. Due to significant lower cost and smaller fabrication time, several microfluidic device manufacturers are already using CO2 laser based processing instead of conventional & time consuming lithographic methods. At least three broadly different strategies can be employed to fabricate microchannels with most of the commercially available low power CO2 lasers i.e. focused cutting, defocused cutting and raster scanning method. These three approaches have been studied in this work as three different fabricating strategies. Further, focused processing method can be employed in two different ways namely single-pass processing and multi-pass processing with their own set of advantages and disadvantages. Similarly, raster scanning method can also be used with a mask as well as without applying mask. Experimental studies have been conducted by fabricating different dimensions of microchannels using these different techniques. Surface quality, cross-sectional profile, microchannel width and heat affected zone have been chosen as parameters for comparing these techniques. Each of these strategies has been discussed in detail. Corresponding analytical models have been outlined for each of these processes. While the single-pass strategy was found to be consuming minimum time, raster scanning method accompanied with masks was observed to be producing microchannel walls with rectangular cross-sections.